Development of Innovative Management Competencies of Students in the Context of Digitization of Education - Qizi, Azizova Makhbuba Khilol; Muhabbat, Hakimova (ASEAN Journal of Educational Research and Technology, 2024)
This study critically examines and advances existing methodologies in project and program portfolio management, aiming to enhance competencies within enterprise project portfolio management. It explores the imperative need for competency development in project portfolio management specialists, underlining its significance for the efficacy of project activities and business operations. The research highlights that current global trends—such as digital transformation, network economy shifts, and transaction cost restructuring—necessitate a revised skill set for project portfolio managers. A significant gap is identified in higher education's role in equipping graduates with the requisite competencies for effective portfolio management. Current educational paradigms often conflate individual project management skills with portfolio management competencies, a misconception prevalent in most modern enterprises. This disconnect is evident when industry leaders advise new graduates to disregard their university training. The findings indicate a significant disparity between the competencies demanded by contemporary businesses for project portfolio and program management and those possessed by university graduates. The study identifies crucial competencies for project portfolio managers and emphasizes the necessity of aligning educational outcomes with business requirements.